IJMMS 27:1 (2001) 7–15 PII. S0161171201010419 http://ijmms.hindawi.com © Hindawi Publishing Corp. ON AN APPLICATION OF ALMOST INCREASING SEQUENCES HÜSEYİN BOR (Received 3 May 2000 and in revised form 25 October 2000) Abstract. Using an almost increasing sequence, a result of Mazhar (1977) on |C, 1|k summability factors has been generalized for |C, α; β|k and |N̄, pn ; β|k summability factors under weaker conditions. 2000 Mathematics Subject Classification. 40D15, 40F05, 40G05. 1. Introduction. A sequence of (bn ) of positive numbers is said to be δ-quasimonotone, if bn → 0, bn > 0 ultimately and ∆bn ≥ −δn , where (δn ) is a sequence of positive numbers (see [2]). Let an be a given infinite series with (sn ) as the α denote the nth (C, α) means of the sequence of its nth partial sums. Let σnα and tn sequences (sn ) and (nan ), respectively, that is, n 1 α−1 An−v sv , Aα n v=0 (1.1) n 1 α−1 An−v vav , Aα n v=1 (1.2) σnα = α = tn where The series α Aα , n=O n α > −1, Aα 0 = 1, Aα −n = 0, for n > 0. (1.3) an is said to be summable |C, α|k , k ≥ 1 and α > −1, if (see [6]) ∞ ∞ 1 α k t α k < ∞, nk−1 σnα − σn−1 = n n n=1 n=1 (1.4) and it is said to be summable |C, α; β|k , k ≥ 1, α > −1 and β ≥ 0, if (see [7]) ∞ ∞ α k α k < ∞. nβk+k−1 σnα − σn−1 = nβk−1 tn n=1 (1.5) n=1 Let (pn ) be a sequence of positive numbers such that Pn = n pv → ∞ as n → ∞, P−i = p−i = 0, i ≥ 1. (1.6) v=0 The sequence-to-sequence transformation Tn = n 1 pv s v Pn v=0 (1.7) 8 HÜSEYİN BOR defines the sequence (Tn ) of the Riesz mean or simply the (N̄, pn ) mean of the sequence (sn ), generated by the sequence of coefficients (pn ) (see [8]). The series an is said to be summable |N̄, pn |k , k ≥ 1, if (see [3]) ∞ Pn k−1 ∆Tn−1 k < ∞, p n n=1 (1.8) and it is said to be summable |N̄, pn ; β|k , k ≥ 1, and β ≥ 0, if (see [4]) ∞ Pn βk+k−1 ∆Tn−1 k < ∞, p n n=1 (1.9) where ∆Tn−1 = − n pn Pv−1 av , Pn Pn−1 v=1 n ≥ 1. (1.10) In the special case when β = 0 (resp., pn = 1 for all values of n), |N̄, pn ; β|k summability is the same as |N̄, pn |k (resp., |C, 1; β|k ) summability. Also it is known that |C, α; β|k and |N̄, pn ; β|k summabilities are, in general, independent of each other. Mazhar [9] has proved the following theorem for |C, 1|k summability factors of infinite series. Theorem 1.1 (see [9]). Let λn → 0 as n → ∞. Suppose that there exists a sequence of numbers (Bn ) such that it is δ-quasi-monotone with nδn log n < ∞, Bn log n is convergent and |∆λn | ≤ |Bn | for all n. If m 1 tn k = O(log m) as m → ∞, n n=1 (1.11) where (tn ) is the nth (C, 1) mean of the sequence (nan ), then the series an λn is summable |C, 1|k , k ≥ 1. Remark 1.2. It should be noted that the condition “ nBn log n is convergent” is enough to prove Theorem 1.1 rather than the conditions “ nδn log n < ∞ and Bn log n is convergent.” 2. The main result. In view of Remark 1.2, the aim of this paper is to generalize Theorem 1.1 for |C, α; β|k and |N̄, pn ; β|k summabilities under weaker conditions. For this we need the concept of almost increasing sequence. A positive sequence (dn ) is said to be almost increasing if there exists a positive increasing sequence (cn ) and two positive constants A and B such that Acn ≤ dn ≤ Bcn (see [1]). Obviously, every increasing sequence is almost increasing but the converse need not be true as can be n seen from the example dn = ne(−1) . Since log n is increasing, we are weakening the hypotheses of the theorem replacing the increasing sequence by an almost increasing sequence. ON AN APPLICATION OF ALMOST INCREASING SEQUENCES 9 Now, we prove the following theorems. Theorem 2.1. Let (Xn ) be an almost increasing sequence and λn → 0 as n → ∞. Suppose that there exists a sequence of numbers (Bn ) such that it is δ-quasi-monotone with nBn Xn convergent and |∆λn | ≤ |Bn | for all n. If the sequence (uα n ), defined by (see [10]) α tn , α = 1, = (2.1) uα α n max tv , 0 < α < 1, 1≤v≤n satisfies the condition m k nβk−1 uα = O Xm n as m → ∞, (2.2) n=1 then the series an λn is summable |C, α; β|k , k ≥ 1 and 0 ≤ β < α ≤ 1. Theorem 2.2. Let (Xn ) be an almost increasing sequence and λn → 0 as n → ∞. Suppose that there exists a sequence of numbers (Bn ) such that it is δ-quasi-monotone with nBn Xn convergent and |∆λn | ≤ |Bn | for all n. If (pn ) is a sequence such that ∞ Pv βk 1 Pn βk−1 1 =O , pn Pn−1 pv Pv n=v+1 m Pn βk−1 tn k = O Xm p n n=1 m Pn βk 1 tn k = O Xm p n n n=1 m λn n=1 then the series n = O(1) as m → ∞, (2.3) as m → ∞, as m → ∞, an λn is summable |N̄, pn ; β|k for k ≥ 1 and 0 ≤ β < 1/k. We need the following lemmas for the proof of our theorems. Lemma 2.3 (see [5]). If 0 < α ≤ 1 and 1 ≤ v ≤ n, then m v α−1 α−1 An−p ap ≤ max Am−p ap . 1≤m≤v p=0 (2.4) p=0 Under the conditions of Theorem 2.2 we obtain the following result. Lemma 2.4. The following equation holds: λn Xn = O(1) as n → ∞. (2.5) 10 HÜSEYİN BOR Proof. Since λn → 0 as n → ∞, we have ∞ ∞ ∞ ∞ ∆λv ≤ λn Xn = Xn ∆λv ≤ Xn Xv ∆λv ≤ Xv Bv < ∞. v=n v=n v=0 (2.6) v=0 Hence |λn |Xn = O(1) as n → ∞. 3. Proof of Theorem 2.1. Let (Tnα ) be the nth (C, α), with 0 < α ≤ 1, mean of the sequence (nan λn ). Then, by (1.1), we have Tnα = n 1 α−1 An−v vav λv . Aα n v=1 (3.1) Applying Abel’s transformation, we get v n−1 n 1 λn α−1 ∆λv Aα−1 A vav , n−p pap + α α An v=1 An v=1 n−v p=1 Tnα = (3.2) so that making use of Lemma 2.3, we have v n n−1 λ α n α−1 α−1 T ≤ 1 ∆λv A pa A va + p v n n−p n−v α α An v=1 A n p=1 v=1 ≤ n−1 1 α α A u ∆λv + λn uα n α An v=1 v v (3.3) α α = Tn,1 + Tn,2 . Since α T + T α k ≤ 2k T α k + T α k , n,1 n,2 n,1 n,2 (3.4) to complete the proof of Theorem 2.1, it is enough to show that ∞ α k <∞ nβk−1 Tn,r for r = 1, 2. (3.5) n=1 Now, when k > 1, applying Hölder’s inequality with indices k and k , where 1/k+1/k = 1, we get m+1 α k nβk−1 Tn,1 n=2 ≤ m+1 n=2 n βk−1 −k Aα n n− v=1 k α Aα v uv Bv ON AN APPLICATION OF ALMOST INCREASING SEQUENCES ≤ m+1 n βk−1 −k Aα n n−1 k−1 Bv n−1 n=2 k α k Aα uv Bv v v=1 = O(1) m+1 nβk−αk−1 n−1 n=2 m 11 v=1 k Bv v αk uα v v=1 k m+1 uα Bv αk 1 1+αk−βk n v=1 n=v+1 ∞ m dx k Bv = O(1) v αk uα v 1+αk−βk x v v=1 = O(1) v m = O(1) v m k k Bv = O(1) v βk uα v Bv v βk−1 uα v v v=1 = O(1) m−1 v=1 v m k k Bm ∆ v Bv r βk−1 uα + O(1)m v βk−1 uα r v r =1 v=1 = O(1) m−1 v=1 ∆ v Bv Xv + O(1)mBm Xm v=1 = O(1) m−1 m−1 v Bv Xv + O(1) (v + 1)Bv+1 Xv+1 + O(1)mBm Xm v=1 v=1 = O(1) as m → ∞, (3.6) by virtue of the hypotheses of Theorem 2.1. Finally, since |λn | = O(1), by hypothesis m m α k k−1 βk−1 α k = λn n nβk−1 Tn,2 un n=1 n=1 = O(1) ∞ m βk−1 α k λn n ∆λv un v=n n=1 ∞ v k ∆λv nβk−1 uα = O(1) v v=1 (3.7) n=1 ∞ Bv Xv < ∞, = O(1) v=1 by virtue of the hypotheses of Theorem 2.1. Therefore, we get m α k = O(1) nβk−1 Tn,r as m → ∞, for r = 1, 2. (3.8) n=1 This completes the proof of Theorem 2.1. Remark 3.1. It is natural to ask whether our theorem is true with α > 1. All we α depends can say with certainty is that our proof fails if α > 1, for our estimate of Tn,1 upon Lemma 2.3, and Lemma 2.3 is known to be false when α > 1 (see [5] for details). 12 HÜSEYİN BOR Proof of Theorem 2.2 . Let (Tn ) denotes the (N̄, pn ) mean of the series Then, by definition and changing the order of summation, we have Tn = n n v 1 1 pv ai λi = Pn − Pv−1 av λv . Pn v=0 P n v=0 i=0 a n λn . (3.9) Then, for n ≥ 1, we have Tn − Tn−1 = n n pn pn Pv−1 λv vav . Pv−1 av λv = Pn Pn−1 v=1 Pn Pn−1 v=1 v (3.10) By Abel’s transformation, we have Tn − Tn−1 = n−1 n+1 pn v +1 pn tn λn − pv t v λ v nPn Pn Pn−1 v=1 v + n−1 n−1 pn v +1 1 pn + Pv ∆λv tv Pv tv λv+1 Pn Pn−1 v=1 v Pn Pn−1 v=1 v (3.11) = Tn,1 + Tn,2 + Tn,3 + Tn,4 . Since Tn,1 + Tn,2 + Tn,3 + Tn,4 k ≤ 4k Tn,1 k + Tn,2 k + Tn,3 k + Tn,4 k , (3.12) to complete the proof of Theorem 2.2, it is enough to show that ∞ Pn βk+k−1 Tn,r k < ∞ for r = 1, 2, 3, 4. p n n=1 (3.13) Since (λn ) → 0 as n → ∞ by the hypothesis of Theorem 2.2, we have m m Pn βk+k−1 Pn βk−1 Tn,1 k = O(1) λn k−1 λn tn k pn pn n=1 n=1 m Pn βk−1 k λn tn = O(1) pn n=1 n Pv βk−1 tv k ∆λn p v n=1 v=1 m Pn βk−1 tn k + O(1)λm pn n=1 = O(1) = O(1) m−1 m−1 ∆λn Xn + O(1)λm Xm n=1 = O(1) m−1 Bn Xn + O(1)λm Xm = O(1) as m → ∞, n=1 (3.14) by virtue of the hypotheses of Theorem 2.2 and in view of Lemma 2.4. ON AN APPLICATION OF ALMOST INCREASING SEQUENCES 13 Now, when k > 1, applying Hölder’s inequality with indices k and k , where 1/k + 1/k = 1, as in Tn,1 , we have m+1 n=2 Pn pn βk+k−1 n−1 m+1 Pn βk−1 1 k k Tn,2 k = O(1) pv λv tv pn Pn−1 v=1 n=2 k−1 n−1 1 pv × Pn−1 v=1 Pn βk−1 1 k−1 k m+1 = O(1) pv λv λv tv pn Pn−1 v=1 n=v+1 βk−1 m k Pv tv λv = O(1) as m → ∞. = O(1) p v v=1 m (3.15) Again, we have m+1 n=2 Pn pn βk+k−1 n−1 m+1 Pn βk−1 1 k Tn,3 k = O(1) Pv Bv tv pn Pn−1 v=1 n=2 k−1 n−1 1 Pv Bv × Pn−1 v=1 Pn βk−1 1 k m+1 Pv Bv tv pn Pn−1 v=1 n=v+1 m Pv βk k Bv tv = O(1) p v v=1 m Pv βk 1 k tv = O(1) v Bv pv v v=1 = O(1) = O(1) m m−1 v ∆ v Bv v=1 i=1 Pi pi βk 1 ti k i m Pv βk 1 tv k + O(1)mBm pv v v=1 = O(1) m−1 ∆ v Bv Xv + O(1)mBm Xm v=1 = O(1) m−1 m−1 vXv Bv + O(1) (v + 1)Bv+1 Xv+1 v=1 + O(1)mBm Xm = O(1) as m → ∞, by virtue of the hypotheses of Theorem 2.2. v=1 (3.16) 14 HÜSEYİN BOR Finally, we have m+1 n=2 Pn pn βk+k−1 m+1 λv+1 k Pn βk−1 1 n−1 tv Tn,4 k = O(1) Pv pn Pn−1 v=1 v n=2 n−1 λv+1 k−1 1 × Pv Pn−1 v=1 v m λv+1 k m+1 Pn βk−1 1 tv = O(1) Pv pn Pn−1 v v=1 n=v+1 m βk 1 tv k λv+1 Pv = O(1) p v v v=1 = O(1) m−1 v ∆λv+1 v=1 r =1 m Pv + O(1)λm+1 p v v=1 = O(1) m−1 Pr pr βk βk 1 tr k r (3.17) 1 tv k v ∆λv+1 Xv+1 + O(1)λm+1 Xm+1 v=1 = O(1) m−1 Bv+1 Xv+1 + O(1)λm+1 Xm+1 v=1 = O(1) as m → ∞, by virtue of the hypotheses of Theorem 2.2 and in view of Lemma 2.4. Therefore, we get m Pn βk+k−1 Tn,r k = O(1) as m → ∞, for r = 1, 2, 3, 4. p n n=1 (3.18) This completes the proof of Theorem 2.2. If we take pn = 1 for all values of n in this theorem, then we get a result concerning the |C, 1; β|k summability factors. References [1] [2] [3] [4] [5] [6] S. Aljančić and D. Arandelović, 0-regularly varying functions, Publ. Inst. Math. (Beograd) (N.S.) 22(36) (1977), 5–22. MR 57#6317. Zbl 379.26003. R. P. Boas, Jr., Quasi-positive sequences and trigonometric series, Proc. London Math. Soc. (3) 14a (1965), 38–46. MR 31#2556. Zbl 128.29302. H. Bor, On two summability methods, Math. Proc. Cambridge Philos. Soc. 97 (1985), no. 1, 147–149. MR 86d:40004. Zbl 554.40008. , On local property of |N, pn ; δ|k summability of factored Fourier series, J. Math. Anal. Appl. 179 (1993), no. 2, 646–649. MR 95a:42002. Zbl 797.42005. L. S. Bosanquet, A mean value theorem, J. London Math. Soc. 16 (1941), 146–148. MR 3,144e. Zbl 028.21901. T. M. Flett, On an extension of absolute summability and some theorems of Littlewood and Paley, Proc. London Math. Soc. (3) 7 (1957), 113–141. MR 19,266a. Zbl 109.04402. ON AN APPLICATION OF ALMOST INCREASING SEQUENCES [7] [8] [9] [10] 15 , Some more theorems concerning the absolute summability of Fourier series and power series, Proc. London Math. Soc. (3) 8 (1958), 357–387. MR 21#1481. Zbl 109.04502. G. H. Hardy, Divergent Series, Clarendon Press, Oxford, 1949. MR 11:25a. Zbl 032.05801. S. M. Mazhar, On generalized quasi-convex sequence and its applications, Indian J. Pure Appl. Math. 8 (1977), no. 7, 784–790. MR 58#29572. Zbl 415.42008. T. Pati, The summability factors of infinite series, Duke Math. J. 21 (1954), 271–283. MR 15,950e. Zbl 057.30002. Hüseyi̇n Bor: Department of Mathematics, Erciyes University 38039, Kayseri, Turkey E-mail address: bor@erciyes.edu.tr